Excellent performance and outstanding resistance to SO2 and H2O for formaldehyde abatement over CoMn oxides boosted dual-precursor hierarchical porous biochars derived from liquidambar and orange peel. (1st June 2022) - Gao, Lei; Yi, Lei; Wang, Jiajie; Li, Xiangyi; Feng, Zhi; Shan, Jian; Liu, Yingyun; Tan, Wenfa; He, Qiuhua; Li, Caiting
Graphical abstract: Highlights: 12%Co0.33 Mn0.67 /HPB exhibited delightful EHCHO and excellent resistance to SO2 and H2 O. The synergistic effect between CoOx and MnOx boosted its physicochemical properties. HPB facilitated active sites accessibility and mass transfer of reactants and products. The HCHO removal mechanism on 12%Co0.33 Mn0.67 /HPB were investigated by in situ DRIFTS. Abstract: This study supplies a facile strategy to design novel carbon-based catalysts with hierarchical porous carrier for the efficient removal of HCHO. A series of CoMn oxides boosted hierarchical porous biochars (CoMn/HPBs) derived from liquidambar and orange peel were synthesized for HCHO removal. The physicochemical properties and removal mechanism of above-mentioned samples were evaluated by means of BET, XRD, SEM, EDX, H2 -TPR, XPS and in situ DRIFTS. 12%Co0.33 Mn0.67 /HPB exhibited delightful EHCHO, favorable thermal stability and excellent resistance to SO2 and H2 O in a wide temperature window from 140 to 360 °C. The inhibitory influences of SO2 and H2 O could defeat the promotional effect of O2 by a narrow margin. Co and Mn co-modified HPB exhibited better performance than that of Co or Mn individually modified HPB, which was attributed to the redox cycle of Mn 4+ /Mn 3+ +Co 2+ ↔Mn 3+ /Mn 2+ +Co 3+ and the synergistic effect between CoOx and MnOx, resulting in more active oxygen vacancies, higher redox ability and better dispersion of metal oxides. Besides, the hierarchical porous structure of support not only furnished abundant surface functional groups, but also facilitated the accessibility of adsorption/catalytic active sites and boosted the convenient mass transfer of reactants and products. Therefore, these superior properties contributed to boosting the catalytic performance, enhancing the thermal stability and perfecting the resistance to SO2 and H2 O. Moreover, both adsorption and catalytic oxidation worked together for HCHO removal over 12%Co0.33 Mn0.67 /HPB. Meanwhile, catalytic oxidation predominated gently with the augmentation of reaction temperature and time.